Impact of sequence stratigraphy, depositional facies, diagenesis and CO2 charge on reservoir quality of the lower cretaceous Quantou Formation, Southern Songliao Basin, China. (May 2018) - Cao, Zheng; Lin, Chengyan; Dong, Chunmei; Ren, Lihua; Han, Shuo; Dai, Junjie; Xu, Xiao; Qin, Mingyang; Zhu, Peng
Abstract: The fourth member of the Lower Cretaceous Quantou Formation in Southern Fuxin Uplift zone of the Southern Songliao Basin is typical tight oil reservoir which has recently been explored and produced. For effective exploration and development, the evaluation and control factors of the reservoir quality of the K1 q4 sandstones should be thoroughly studied. The study focused on the control of the combination of sequence stratigraphy, depositional facies and diagenesis on the reservoir quality, and identified the impact of CO2 charging, based on the core and thin section observation, XRD, SEM, fluid inclusion and isotope testing and analysis. The fourth member of the Lower Cretaceous Quantou Formation consists of lowstand system tracts (LST), transgressive system tracts (TST) and highstand system tracts (HST). The K1 q4 sandstones were mostly deposited in distributary channels and crevasse splays of a delta plain within the LST and TST, and underwater distributary channels and sheet sands of a delta front within the HST. The K1 q4 sandstones, mostly silt to medium grained, medium to well sorted, and are mostly lithic arkoses and feldspathic litharenites, have undergone significantly diagenetic alterations, such as compaction, quartz cementation, unstable grains (feldspar and volcanic fragments) dissolution, carbonate cementation and clay minerals cementation. The reservoir quality of the K1 q4 sandstones are poor with low porosity and permeability, showing variations among the different system tracts and depositional facies, and are influenced by the charging of CO2 and controlled by the combination of sequence stratigraphy, depositional facies and diagenesis. The sandstones with high reservoir quality are mostly deposited in high energy environments, including the (underwater) distributary channel sandstones, especially the LST distributary channel sandstones with the best reservoir quality among the LST, TST and HST sandstones, which can be ascribed to larger grain size and better sorting resulting in larger intergranular pore space after compaction, and less content of carbonate cements, illite and mixed-layer I/S, and more pore-lining chlorite and more effectively dissolution. The poor reservoir quality of sandstones from crevasse splay and sheet sand is due to the small grain size and bad sorting which resulted in extensive compaction and the resulting weak dissolution. The charging of CO2 has dual impact on the reservoir quality of the K1 q4 sandstones. The CO2 charging can induce the dissolution of unstable detrital grains and the precipitation of dawsonite. The former create new secondary pore space, while the latter occupy the intergranular pore space. The CO2 charging is harmful to the reservoir quality when the dawsonite content exceeds a threshold of 5%. Highlights: The K1q4 sandstones were deposited in deltaic environment within LST, TST and HST. The inorganic CO2 participated the precipitation process of carbonate cements. The LST distributary channel sandstones have the best reservoir quality. The controlling factors of the reservoir quality differences were identified. CO2 charging destroyed the reservoir quality when the dawsonite content exceeds 5%.